The Plurality of Human Brain-Computer Interfacing. - Mueller-Putz, G.; Millán, José del R; Gerwin Schalk; Mueller, K.R. (Proceedings of the IEEE, 2015)
The articles in this special issue focus on brain-computer interfacing. The papers are dedicated to this growing and diversifying research enterprise, and features important review articles as well as some important current examples of research in this area. The field of brain-computer interface (BCI) research began to develop about 25 years ago and transformed from initially isolated demonstrations by a few groups into a large scientific enterprise that is currently producing hundreds of peer-reviewed articles and several dedicated conferences and workshops each year. This level of productivity is reflective of the large and continually growing enthusiasm by the scientific community, funding agencies, and the public.
Keywords: Brain-computer interface (BCI)